(untitled) (Altre Modernità, 2017)
Contemporary (especially women’s) “Afropolitan” narrations portray multiple and displaced identities, developed in fragmented and diversified spaces. New global geographies including African countries, Great Britain and the United States encompass migrating characters, not belonging to any nation, yet, at the same time, to all of them. In Ghana Must Go (2013) Taiye Selasi points to the issue of cultural, ethnic and linguistic mixture, through a non-linear textual construction, where spaces and times are multiple, the main events are intermixed with flashbacks, different points of view alternate and overlap. Selasi’s novel, the title of which refers to the bags used by the Ghanaian refugees driven away from Nigeria in 1983, is divided into three sections (“gone-going-go”), and basically narrates the story of Kweku (a Ghanaian surgeon) and Fola (his Nigerian wife) and of their “American” family, of their four children, born and educated in the USA, successful professionals, artists, scholars, but weak and problematic individuals. The Sai family is scattered in different places and only shares the same experience after the death of their father, moving back from America to Ghana. The characters’ identity is mobile and their home is not based in a specific place but lies in their familiar and affective ties. In a transnational context, Ghana Must Go focuses on the final recomposition of a dislocated family, through a narration that displays the fragility of contemporary relationships across gender, ethnicity, cultures and languages.